The Effect of Group Counseling on Reducing Aggressive Behavior in Adolescent Students - Malim Soleh Rambe; Azijah Tussolihah Siregar; Laila Kalsum Hasibuan (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2025)
This study examines the influence of group guidance on reducing aggressive behavior among adolescent students, a psychosocial issue that frequently arises in school settings and adversely affects emotional stability, social adjustment, and academic performance. Using a quantitative approach with a one-group pretest–posttest design, the study involved 12 students identified as having high levels of aggression through purposive sampling. The aggression scale used consisted of 50 items, with 49 validated and a reliability coefficient of α = 0.975. The group guidance intervention was conducted in four structured sessions that focused on recognizing aggressive behavior, improving emotional regulation, developing empathy, and strengthening conflict-resolution skills. Results of the Wilcoxon Signed Rank Test indicated a significant decline in aggressive behavior, with the mean score decreasing from 106.83 in the pretest to 84 in the posttest (p = 0.003 < 0.05). These findings demonstrate that group guidance is effective in reducing aggressive tendencies by enhancing students’ emotional awareness and their ability to respond positively in social interactions. The study concludes that group guidance can serve as a practical preventive intervention in schools to promote students' social competence and minimize aggressive behavior. Keywords: group guidance, aggressive behavior, adolescents, emotional regulation